U-shaped association between serum albumin and pediatric intensive care unit mortality in critically ill children - Zhang, Xuepeng; Zhang, Lifan; Wei, Canzheng; Feng, Liwei; Yang, Juqin; Zhang, Geng; Lu, Guoyan; Gui, Xiying; Zhou, Yue; Yang, Kaiying; Zhou, Jiangyuan; Zhou, Xinle; et al. (Frontiers in Nutrition, 2022)
Introduction: The detailed association between albumin levels and mortality has not been studied in critically ill children. The aim of this study was to reveal an association between albumin levels in detail and mortality in critically ill children. Methods: We retrospectively collected data from children admitted to four pediatric intensive care units (PICUs) in China between January 2015 and October 2020. Restricted cubic spline curves based on logistic regression models were generated to evaluate the detailed associations between serum albumin levels and PICU mortality. Threshold effect analysis was performed using two piecewise regression models. Results: The study included 9,123 children. The overall mortality was 5.3%. The detailed association between serum albumin levels and the risk of mortality followed a U-shape. The risk of mortality decreased with increasing serum albumin levels (OR = 0.919; 95% CI: 0.886, 0.954) in children with serum albumin levels < 43.2 g/L and increased with increasing serum albumin levels (OR = 1.174; 95% CI: 1.044, 1.316) in children with serum albumin levels 43.2 g/L. Conclusion: There was a U-shaped association between serum albumin levels and mortality in critically ill children in the PICU.